Malpositioned Lines and Tubes on Chest Radiograph – A Concise Pictorial Review - Sakthivel, Muthu Kumar (J Clin Imaging Sci, 2020)
A wide variety of cardiothoracic support devices are used in intensive care units and few of these devices are increasingly being utilized in outpatient settings as well. A meticulous assessment of these lines and tubes by the interpreting radiologist is cardinal since malpositioned lines and tubes can significantly impact the functioning of these devices and may result in potential complications affecting the clinical outcomes. The purpose of this article is to illustrate the normal positioning and malpositioning of the routinely used support lines and tubes identified on chest radiographs.